In vitro antiviral activity of seeds from Guettarda angelica against avian viruses - Alyne Vieira Barrosa & c, Aline Oliveira da Conceiçãob, Isabela Cristina Simonia, Marina Aiello Padillaa & c, Maria Judite Bittencourt Fernandesa, Clarice Weis Arnsc (Journal of Applied Pharmaceutical Science, 2013)
The aim of this study was to evaluate the inhibition of the aqueous extract of seeds (AEs) from Guettarda angelica on cell infection by two avian RNA viruses: avian reovirus (ARV) and metapneumovirus (AMPV). The cytotoxic and antiviral activities were evaluated by MTT assay to determine the 50% cytotoxic (CC50) and inhibitory concentrations (IC50). The selectivity index (SI=CC50/IC50) also carried out. AEs exhibited antiviral activity only against ARV presenting IC50 of 23.59µg/mL. This inhibition was not due to any cytotoxic effect of AEs since the CC50 on Vero cells was of 400.60µg/mL and its SI was of 17.00; this extract also showed a virucidal effect on ARV. Previous studies also demonstrated antiviral activity of AEs extract against three animal herpesviruses. Thus, the seeds from G. angelica showing antiviral activity against DNA and RNA viruses, enveloped and non-enveloped, could be promising source of new antiviral agents encouraging its fractionation to isolate the active compound.
Keywords: Guettarda angelica, seeds, avian